Embedded System Practicum Module for Increase Student Comprehension of Microcontroller - Indrianto Indrianto; Meilia Nur Indah Susanti; Rakhmat Arianto; Riki Ruli A. Siregar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The result of applying the embedded system in education for students is successfully applied in university. On the other side, many people in Indonesia use smart equipment’s (Hand phone, Remote), but none of those equipments are used in education. University as the source of knowledge should overcome the problem by encouraging the students to use a technology with learning about it first. Embedded System Practicum Module Design needs a prototype method so that the practicum module that is desired can be made. This method is often used in real life. A prototype considered of a part of a product that expresses logic and physical of external interface that is being displayed and this method will fully depend on user contentment. Embedded System Practicum Module Design is made to increase student comprehension of embedded system course and to encourage students to innovate, so that many technologies will be developed and also to help lecturers deliver course subjects. With this practicum it is hoped that the student comprehension will increase significantly. The result of this research is a decent practicum module, hardware or software that can help students to know better about technology and the course subjects so that it will encourage the students to create an embedded system technology. The result of the test has been done; there is an increase of learning value obtained by 7.8%.